Jual Beli Hewan Peliharaan di Kota Jambi Perspektif Hukum Islam - Syamsu Hadi (Universitas Batanghari Jambi, 2023)
At present, the practice of buying and selling pets in the city of Jambi in increasing. Animals such as dogs, cats, rabbits, hamsters, birds, fish, even some who keep snakes as pets. People’s interest in pets is usually because pets can become human substitutes (as friends and family), as house keepers or protectors, and as a self-reflection (hobby). In connection with the practice of buying and selling pets that occur in the community lately, as a Muslim, we should care about these issues, especially in the matter of buying and selling because objects that are traded and sometimes do not get treatment as it should, other than that animals that are traded also sometimes are animals which is forbidden in Islamic law. By using the approach of social science and Islamic law, the authors can conclude that in the city of Jambi, especially in the Subdistrict of Telanaipura and Pasar Kota Jambi, there is a pet trade activity with an online store system and online stores. Factors that cause pet trade are usually due to economic factors and opportunities. Meanwhile, there are two points according to Islam regarding the law of pet trade, which is permissible if the animal is benign and not harmful; and should not be if the animal is wild and dangerous.